Building Learning Loyalty through Teacher Competence: The Role of Teacher Role Modeling and Student Satisfaction - Adibah Adibah; A.M Maqdum Biahmada; Rofiatul Hosna (JUMPA : Jurnal Manajemen Pendidikan, 2025)
Sustaining students' commitment to learning remains a persistent challenge in Islamic Religious Education, particularly after the disruptions of the pandemic period. This study examines how teacher competence shapes student learning loyalty, and whether teacher role modeling and student satisfaction help explain that relationship at SMP Romly Tamim Surabaya. A quantitative survey was distributed to all 120 students through saturated sampling, and the data were analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS. The results were unexpected. Teacher competence showed no significant effect on either student satisfaction or learning loyalty. Teacher role modeling, by contrast, exerted a strong and significant influence on both, and student satisfaction significantly predicted loyalty while mediating the link between role modeling and loyalty. What students seem to value is not technical teaching skill alone but the moral example their teachers set in daily conduct. One caveat deserves attention, namely that the role modeling construct fell short of conventional validity thresholds, so its dominant role should be read as indicative rather than conclusive. Schools are therefore encouraged to treat teachers' character formation and exemplary behavior as professional standards on par with pedagogical competence, not as an afterthought.